PERBAIKAN TIMBUNAN OPRIT JEMBATAN MENGGUNAKAN MORTAR FOAM DENGAN KONDISI TANAH YANG MENGALAMI PENURUNAN - M. Alit Suryawan; Sari, Gusti Ayu Sukma Dwi Naindia; Saputra, I Nyoman Arya; Prabawa, I Made Angga (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Repair work on the patro papri toll road at km 146 + 950 Cipamongkolan bridge whose base soil has decreased due to loading on it (settlement) so that there is a gap or a deep horizontal small groo, the innovation of the work method used to fix the problem is to combine the injection method of grouting cement slurry with mortar foam material, the tool used has an injection capacity specification of 15-30 m3/h with a pressure of 3 HP and power of 1 phase, the incorporation of this method has the purpose of cost efficiency of repair with the comparison of the price of cement slury injection which is usually used as an injection material for the repair of structures that have a gap per m3 is Rp. 10,800,000.00 while foam mortar is Rp. 3,500,000.00, the required density target is 800 KPa at the age of 28 days, the use of sand composition from the gedebage area as the main material with the type of intermediate gradation with The provision of passing the 3/8 filter by 100% and no passing the 200 filter produces a quality that exceeds the quality target, which is 918.05 KPa at the age of 28 days The advantages possessed by this mortar foam material are light weight, do not shrink, and do not require a compaction process when used to replace the basic soil. Keyword: Injection.Foam Mortar.Gap